Pembuatan Pot Dengan Pemanfaatan Limbah Kain Atau Handuk Bekas di Dusun Bangunrejo, Tridadi, Sleman, D.I Yogyakarta - Nilasari Wareh Utari; Alvi Khusniatun Nisa'; Mas Sulthon Mustafid; Bita Ardila Merdeka Wati; Zahrotunnisa Damar Amanah; Heru Subaris Kasjono; Sri Haryanti (JPS : Jurnal Pengabdian Serulingmas, 2023)
Garbage or fabric waste is an environmental problem that is no less serious than plastic waste. Fabric waste is a type of inorganic waste that is difficult to decompose and cannot be composted, but if burned it can produce smoke and toxic gases which are harmful to the environment. Garbage or waste in the form of used fabric or towels can be further processed through a process that turns the used materials into useful items such as pots. Bangunrejo Villager participation in fabric waste management remain low and they don’t have knowledge about proper fabric waste management. Therefore, a community service team from Environmental health major of Poltekkes Yogyakarta initiated the program of fabric waste management education and pot making from fabric waste. This activity aims to minimize the problem of fabric waste and increase community knowledge about fabric waste management. The activity began with socialization, namely discussions and lectures related to the purpose and benefits of pot-making activities, then the activities continued with demonstrations and hands-on practice of making pots with used cloth and painting pots. This activity was followed well and enthusiastically by the participants, this can be seen in the reactions of the participants who actively asked. Through this pot-making activity, it is hoped that the people of Bangunrejo Village can protect the environment by utilizing or recycling household waste or waste into useful products.